A custom-made conformer wrapped in lower oral mucosa for the correction of severely contracted socket. Issue 6 (November 2021) - Yang, Fan; Li, Zhengkang; Deng, Yuan
Purpose: To investigate the clinical effects of a custom-made conformer wrapped in lower oral mucosa for the correction of severely contracted socket. Methods: Clinical data and photographs of 32 patients with severely contracted socket were retrospectively analyzed. Among the 32 cases, 21 were males and 11 were females. Their ages ranged from 20 to 71 years (mean, 45 years). Each patient underwent conjunctival sac plasty using a custom-made conformer wrapped by oral mucosa, then compression bandage for 1 month. All patients received tarsorrhaphy 6 months postoperatively, and an artificial eye was worn 1 week later. Results: All the grafts were fully vascularized. The conjunctival sacs had enough space to fit the desirable artificial eyes, and adequate aesthetic outcomes were reached postoperatively. The mean depth of the upper fornix was 4.28 ± 0.66 mm preoperatively and 18.84 ± 0.65 mm postoperatively ( p  < 0.01), and lower fornix depth was 2.69 ± 0.42 and 8.78 ± 0.82 mm, respectively ( p  < 0.01). Lower lip deformity occurred in one case. Conclusion: A custom-made conformer wrapped in lower oral mucosa was a safe and effective grafting material. The grafts can be effectively used in the reconstruction of severely contracted socket and lead to good cosmetic outcomes.